2013
DOI: 10.1037/a0030394
|View full text |Cite
|
Sign up to set email alerts
|

Quebec psychologists and continuing education.

Abstract: Continuing education is an integral ingredient in the maintenance and development of essential competencies in professional psychology. However, there is a lack of knowledge and investigation into the continuing education practices, needs, interests, attitudes, and modality preferences among practicing psychologists, particularly those practicing in Canada. Essential aspects of continuing education among a sample of 418 licensed psychologists in clinical practice in Quebec were examined. Professional reading, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
1
5
0
1
Order By: Relevance
“…However, this study's sample characteristics are similar to those of a larger study of clinical psychologists across Canada (Ionita & Fitzpatrick, 2014). Further, the psychologists from Quebec in this study had similar characteristics to a larger sampling of Quebec psychologists reported by Bradley and Drapeau (2013). Nevertheless, one should be cautious about generalizing from this study's samples.…”
Section: Limitationssupporting
confidence: 68%
See 1 more Smart Citation
“…However, this study's sample characteristics are similar to those of a larger study of clinical psychologists across Canada (Ionita & Fitzpatrick, 2014). Further, the psychologists from Quebec in this study had similar characteristics to a larger sampling of Quebec psychologists reported by Bradley and Drapeau (2013). Nevertheless, one should be cautious about generalizing from this study's samples.…”
Section: Limitationssupporting
confidence: 68%
“…These findings cannot be attributed to differences in theoretical orientation or level of education, which were controlled in the analysis. Recently, Bradley and Drapeau (2013) conducted a survey of preferences and needs for continuing education among psychologists in Quebec. The vast majority indicated the importance of maintaining their competence throughout their career, particularly in the domain of psychological interventions.…”
Section: Top-rated Psychotherapy Research Themesmentioning
confidence: 99%
“…Or, les activités de supervision ne sont pas restreintes aux dyades étudiant-professionnel; elles s'appliquent également aux dyades professionnel-professionnel. Plus des deux tiers des psychologues québécois ayant répondu a `un sondage ont inscrit la supervision par les pairs parmi les activités de formation continue qu'ils préféraient (Bradley & Drapeau, 2013). D'ailleurs, depuis l'avènement du projet de loi 21 au Québec encadrant la pratique de la psychothérapie, les professionnels qui exercent la psychothérapie doivent recevoir de la supervision dans leurs activités de formation continue (a `raison d'un minimum de cinq heures a `tous les cinq ans).…”
Section: Supervision Par Les Pairs : Données Précises Sur La Supervis...unclassified
“…Unsurprisingly, many health professions and many regulatory bodies and licensing boards have made CE mandatory for the professionals whose practice they oversee or regulate. However, in Canada, many of the provinces have not yet implemented mandatory CE for psychologists and there is a dearth of research regarding the CE practices of Canadian psychologists (Bradley & Drapeau, 2013).…”
mentioning
confidence: 99%